Implikasi Brexit Terhadap Keamanan Kolektif di Kawasan Eropa - Irzady, Alif Rangga; Nugraha, Imam Fadhil (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the implications of Brexit on collective security in Europe, highlighting the dynamics resulting from the UK’s withdrawal from the European Union. Brexit signals a significant change in the security architecture of Europe, considering that the UK is one of the countries with the largest military and economic capabilities in the region. Brexit has created new challenges for the European Union in maintaining the effectiveness and integration of collective security in the region, and has triggered a shift in dominance toward countries such as Germany and France, which are vying for the position left vacant by the United Kingdom post-Brexit. This study employs a descriptive qualitative approach with a collective security perspective as an instrument to analyze the impact of Brexit on security cooperation in the European region. The findings indicate that Brexit not only weakens the cohesion of the European Union but also drives efforts to adjust security strategies within the European Union. This research clarifies that while Brexit is often referred to as a test for European collective security, the principles of cooperation and adaptation of security policies remain the key to maintaining security stability in the European region in response to evolving geopolitical challenges.